Occupational Medicine in Italian Academy: what future? - Apostoli, Pietro (La Medicina del Lavoro, 2017)
The entire Italian University system, including the whole field of medical teaching and research, is currently passing through a period of cumbersome changes due to the many difficulties encountered in its reform process. Academic occupational medicine is deeply involved in this process that resembles a real crisis. Given this background, this contribution - written as President of the Italian College of Occupational Medicine Full Professors - has the main objective to open a debate about the current generalized crisis of our Academic Discipline and about its possible future developments. Questions that appear most relevant to the nearly forty University Institutes we are working in include: The constantly decreasing number of professors and researchers (presently about 20 full professors, 50 associate professors and 60 researchers); the reduced ability to recruit young researchers; the contraction of resources and funds; the difficult coordination with other clinical and prevention disciplines in teaching activities. Despite this, points of scientific and professional excellence in many fields exist in our Institutes: from toxicology and epidemiology, to respiratory diseases and ergonomics, to evidence based prevention and quality systems promotion. The expected debate should facilitate new organizational links within and across Universities in order to gain critical masses, improve capabilities in new fields of research (as dose and effect indicators and their matrices, epigenetics, exposomics, connection of exposure data with epidemiological evidences), innovate and expand teaching (in Medical Schools courses and in Residency programs), and advance clinical-diagnostic practices in University Hospitals.